2009
DOI: 10.1016/j.placenta.2008.10.010
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Plasticity of the Microscopic Placental Architecture in Relation to Litter Size Variation in the Common Marmoset Monkey (Callithrix jacchus)

Abstract: Fetal demand, shaped by factors such as number of fetuses, may alter placental regulation of exchange, even when maternal nutrition restriction is not overt. The marmoset is an interesting model in which to examine this aspect of placental function due to unique placentation that leads to multiple fetuses sharing a unified placental mass. We demonstrated previously that the triplet marmoset placenta exhibits significantly higher efficiency than does the twin placenta. Here, we test the hypothesis that this inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
33
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 39 publications
3
33
0
Order By: Relevance
“…In sheep twin litters, not only is total placental mass increased compared to that of singletons (Dwyer and others 2005), but total surface area of the interface is increased as well (Kaulfuss and others 2000). Microscopic analysis of the marmoset placenta in relation to litter size reveals a similar pattern (Rutherford and Tardif 2009). Twin and triplet placentas did not differ significantly in total volume or the volumes of individual placental compartments (e.g.…”
Section: Dissecting Intrauterine Dynamics Via Placental Plasticity Inmentioning
confidence: 88%
See 3 more Smart Citations
“…In sheep twin litters, not only is total placental mass increased compared to that of singletons (Dwyer and others 2005), but total surface area of the interface is increased as well (Kaulfuss and others 2000). Microscopic analysis of the marmoset placenta in relation to litter size reveals a similar pattern (Rutherford and Tardif 2009). Twin and triplet placentas did not differ significantly in total volume or the volumes of individual placental compartments (e.g.…”
Section: Dissecting Intrauterine Dynamics Via Placental Plasticity Inmentioning
confidence: 88%
“…In a study of 26 marmoset full-term pregnancies, Rutherford and Tardif (2009) determined that whereas total litter mass was significantly greater in triplet litters (a difference of nearly 30%), placental mass was not significantly different from that of twins. Triplet placentas are thus smaller than twin placentas, relative to fetal mass.…”
Section: Dissecting Intrauterine Dynamics Via Placental Plasticity Inmentioning
confidence: 99%
See 2 more Smart Citations
“…A survey of marmoset placentas from nonrestricted twin and triplet litters has found that the placenta can be plastic in structure and function in the face of differing litter sizes (Rutherford and Tardif, 2008). The structure and size of marmoset placentas from singleton, twin, and triplet litters have been found to significantly differ from each other (Rutherford, 2009;Rutherford and Tardif, 2008). Triplet infants are predominately born at a lower individual body weight than twin infants; however, the overall infant weight of the litter is significantly larger in triplets.…”
Section: Example 1: Explanations For Litter Size In Callitrichid Primmentioning
confidence: 99%